Bromophenols in Marine Algae and Their Bioactivities - Liu, Ming (Molecular Diversity Preservation International, 2011)
Marine algae contain various bromophenols that have been shown to possess a variety of biological activities, including antioxidant, antimicrobial, anticancer, anti-diabetic, and anti-thrombotic effects. Here, we briefly review the recent progress of these marine algal biomaterials, with respect to structure, bioactivities, and their potential application as pharmaceuticals.